Effect of Gluelines for Mengkulang Glulam Dowel-Bearing Strength - Jihan Abd Malek, Nor; Abdulrahman Mohammed Ali, Ali; Zukri Wan Abdullah, Wan; Ibrahim, Azmi; Hassan, Rohana (International Journal of Engineering and Technology, 2018)
Malaysia is one of the tropical countries around the world which is the pioneer in timber harvesting. Mengkulang is known for its strength and durability. In timber construction, connection is the most important part. The strength of timber has huge impact of the connection strength and the whole structure. Furthermore, timber strength connections also depend on the factor affecting which is bolt diameters and end distances. The objectives of this research are to determine the dowel-bearing strength for 12mm, 16mm and 20mm bolt diameter thus to compare the dowel-bearing strength between glue line and without glue line. The dowel-bearing strength test was tested on Mengkulang timber species for different dowel diameters which are 12mm, 16mm and 20mm for with and without glue line parallel to the grain using half-hole test. The dowel-bearing strength, Fy values of 5% diameter offset-load, F5% are obtained from load versus displacement graph using ASTM D5764-97a. The dowel-bearing strength, Fy for 20mm diameter with glue line showed 14.71 N/mm2 higher than 16mm diameter and 12mm diameter with 14.44 N/mm2 and 11.63 N/mm2 accordingly. While, the dowel-bearing strength, Fy for 20mm diameter without glue line showed 15.64 N/mm2 higher than 16mm diameter and 12mm diameter with 14.71 N/mm2 and 14.44 N/mm2 respectively. In conclusion, the bigger diameter the higher dowel-bearing strength and the dowel-bearing strength for without glue line showed higher than dowel-bearing strength with glue line.Â Â